Psychotherapeutic Art Education Method (PAEM) for reducing anxiety and depression in Indonesian undergraduates - Santiago Paul Erazo Andrade; Juju Masunah; Rita Milyartini (Gelar: Jurnal Seni Budaya, 2025)
This study applied arts-based research with supportive quantitative indicators to design, implement, and evaluate the Psychotherapeutic Art Education Method (PAEM), a structured four-practice art process (Meditation Art Drawing, Psychic Art, Dreaming Art Painting, and Art Discussion) based on the active imagination of Carl Jung and systematized by Comandini (2019). It aims to explore if PAEM could reduce symptoms of anxiety and depression and increase the art & imagination expression among undergraduate students. Ten students from different majors at Universitas Pendidikan Indonesia, who reported mild to moderate emotional distress, participated in two weekend workshops in December 2024. Data were collected through validated pre- and post-questionnaires for mental health and art & imagination scales, reflective portfolios, voluntary Socratic reflections, and symbolic analysis of artworks. Triangulation combined quantitative scores, thematic analysis of written and oral reflections, and Jungian interpretation of visual archetypes. Findings showed a 38.1% reduction in the mean mental health indicator (from 3.78 to 2.34 on a 5-point scale) and a 10.8% increase in art & imagination scores (from 3.32 to 3.68). Participants’ artworks consistently revealed Jungian archetypes, linked to personal narratives of trauma, isolation, and resilience. Students described feeling “lighter,” less alone, and more accepting of difficult emotions. The study offers an initial empirical bridge between Jungian depth psychology and art education practice in the Indonesian university context, creating a safe, non-stigmatizing, and profoundly meaningful space where addressing mental health remains difficult. Even though these ten stories are truly worth telling, this research encourages larger studies in the future.